Legal and Organisational Measures for Protecting Monuments Against Flooding: Learning from the 2024 Flood - Bryczek-Wróbel, Patrycja; Kochanowicz, Małgorzata (Roczniki Nauk Społecznych, 2026)
The publication focuses on legal and organisational measures serving to protect cultural heritage during flooding, considered in the context of events that took place in Poland in September 2024. Our aim was to identify legal and organisational tools for protecting cultural heritage, such as monuments, during times of flooding. The article employs theoretical methods, such as review and analysis of legal and organisational measures for protecting monuments against flooding. Government and ministerial documents as well as relevant literature were analysed. Our analysis was descriptive and analytical and relied on secondary data. Of the many legal and organisational measures serving to protect monuments from flooding and respond to their consequences, the following measures should be highlighted: law, governmental guidelines, national and international aid programmes, appointment of a coordinator for the protection of monuments in the event of flooding, the creation of national financial reserves, and international cooperation.